2020
DOI: 10.37265/japiv.v9i2.27
|View full text |Cite
|
Sign up to set email alerts
|

Vietnam Construction Industry Performance Issues and Potential Solutions

Abstract: This paper provides a literature review assessing the performance and issues of delivering construction services in the Vietnam Construction Industry (VCI). The research also explores a potential solution that could improve the performance of the VCI. The results show multiple non-performance issues that the VCI has experienced in the past 15 years, and presents a comparison between these issues and issues from other countries. The results reveal that the top 5 non-performance issues in the VCI include poor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…• Toor and Ogunlana (2007) examined the causes of construction delays in Thailand and found that the most significant problems were the lack of standardization in design, lack of contractor's experience and control over project, inadequate experience of staff, lack of competent subcontractors/supplies, unrealistic project schedule, lack of responsibility, contractor's financial difficulties, poor contract management, poor site access or availability, and poor efficiency of supervisor or foreman. • In particular to Vietnam, Le (2017) reviewed 100+ peer-reviewed manuscripts of the construction industry in Vietnam in the last 15 years and found 23 non-performance causes, out of which, the top five factors by appearance frequency included ineffective designs and frequent design changes, poor contractor performance, ineffective project management, financial difficulties of owner, and financial difficulties of contractor. Further, the authors also compared risks found in Vietnam to those occurred elsewhere in other developing countries and suggested that 91% of them are similar.…”
Section: Introductionmentioning
confidence: 99%
“…• Toor and Ogunlana (2007) examined the causes of construction delays in Thailand and found that the most significant problems were the lack of standardization in design, lack of contractor's experience and control over project, inadequate experience of staff, lack of competent subcontractors/supplies, unrealistic project schedule, lack of responsibility, contractor's financial difficulties, poor contract management, poor site access or availability, and poor efficiency of supervisor or foreman. • In particular to Vietnam, Le (2017) reviewed 100+ peer-reviewed manuscripts of the construction industry in Vietnam in the last 15 years and found 23 non-performance causes, out of which, the top five factors by appearance frequency included ineffective designs and frequent design changes, poor contractor performance, ineffective project management, financial difficulties of owner, and financial difficulties of contractor. Further, the authors also compared risks found in Vietnam to those occurred elsewhere in other developing countries and suggested that 91% of them are similar.…”
Section: Introductionmentioning
confidence: 99%
“…BVA was identified by all three countries as a solution that could potentially work in improving construction efficiency and performance. The solution met all the requirements and constraints of the VCI, KSACI, and ICI (Nihas, 2013;Le, 2017).…”
Section: Literature Research On Vietnam Saudi Arabia and India Identmentioning
confidence: 92%
“…In reviewing papers available on an on-line community called Research Gate it was found that the BVA Saudi Arabian articles had more than 1852 reads, showing the interest in the KSACI community (Research Gate, 2018). Vietnam also had a Ph.D. candidate that is performing research on its implementation of the BVA (Le, 2017). India had a master's student perform preliminary research on its potential implementation of the BVA.…”
Section: Literature Research On Vietnam Saudi Arabia and India Identmentioning
confidence: 99%
“…A major issue for Facility Managers (FMs) is that the procurement department of organizations does not allow professional FMs to identify, select and utilize expert vendors (Rivera & Kashiwagi, 2016a, 2016bLe, 2017). Traditional procurement processes often force the FM to accept the low-price vendor (D. Kashiwagi, J. Kashiwagi, Child, & Sullivan, 2014;Kashiwagi, 2015a).…”
Section: Introductionmentioning
confidence: 99%